Abnormalities of Otoacoustic Emissions in Myasthenia Gravis: Association With Serological and Electrophysiological Features - Choi, Jongsuk; Kim, Nam-Hee; Park, Soo-Hyun; Cho, Chang Gun; Lee, Hyo-Jeong; Kim, Sung Un; Park, Kyung Seok (Frontiers in Neurology, 2018)
Objective: To investigate whether otoacoustic emissions (OAEs) are impaired in patients with myasthenia gravis (MG) and whether such dysfunction is associated with serological and electrophysiological features of MG. Methods: We tested 15 patients with MG (30 ears) and 10 healthy age- and sex-matched subjects (20 ears) for transiently evoked OAE (TEOAE) and distortion product OAE (DPOAE). Results: Compared with controls, MG patients revealed a significant reduction in the amplitude of TEOAEs (p < 0.05) and DPOAEs at higher frequencies between 2,026 and 4,053 Hz (p < 0.05). In the subgroup analysis, TEOAE and DPOAE amplitudes were significantly lower in the acetylcholine receptor (AChR) antibody-positive group (p < 0.05) as well as in the repetitive nerve stimulation (RNS)-positive (p < 0.05) group. In particular, the OAE alteration significantly correlated with anti-AChR antibody titers. No significant difference of the OAEs was found between thymomatous and non-thymomatous MG or between purely ocular and generalized MG. Conclusions: Our study confirms that OAEs reveal subclinical dysfunction of the cholinergic neurotransmission of cochlear outer hair cells and correlate well with electrophysiological and serological characteristics of MG patients. Our findings imply that the measurement of OAEs might increase the diagnostic accuracy and help to monitor the severity of MG.